2014
DOI: 10.1097/id.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Implant-Supported Fixed Prosthesis in a Hypohidrotic Ectodermal Dysplasia Patient

Abstract: In ED patients, NDI together with immediate implant placement can be used successfully to support a complete fixed restoration and should be considered as an alternative to major reconstruction surgeries. Key factors associated with increased predictability are discussed together with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Even if a comprehensive preoperative evaluation is always necessary and customized to each patient, implant supported restorations are considered the treatment of choice in ED patients for their superior function (8). Several authors reported that ED patients showed normal healing and osseointegration rates comparable to healthy controls (10,12,22,34,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if a comprehensive preoperative evaluation is always necessary and customized to each patient, implant supported restorations are considered the treatment of choice in ED patients for their superior function (8). Several authors reported that ED patients showed normal healing and osseointegration rates comparable to healthy controls (10,12,22,34,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the craniofacial district, the most common anatomical features are maxillary hypoplasia, mandibular protrusion, midface depression, reduced facial height, frontal bulging, abnormal or missing sweat glands, hypotrichosis, dry skin, protuberant lips, saddle nose (6)(7). Furthermore, oral manifestations are also frequently observed including hypodontia, defective enamel, peg shaped teeth, delayed dental eruption and severe alveolar ridge deficiency (8). Hypodontia is the most frequently found sign of oral anomalies, with an estimated prevalence of 80% in ED patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%